Optimizing bioethanol production from sweet sorghum stem juice under very high gravity fermentation and temperature stress conditions - Phon Thatiyamanee; Pattana Laopaiboon; Lakkana Laopaiboon (Carbon Resources Conversion, 2025)
This study optimized ethanol production from sweet sorghum stem juice (SSJ) by Saccharomyces cerevisiae NP01 under very high gravity (VHG) fermentation in 500-mL air–locked flasks at 30 °C. Response surface methodology based on a Box-Behnken design was employed to optimize initial sugar (267 g/L), urea (3.24 g/L), and cell concentration (1.32 × 108 cells/mL) for maximization of ethanol concentration (PE), productivity (QP), and sugar consumption (%SC). The experimental values (PE, 119.29 g/L; QP, 2.49 g/L.h and %SC, 91.83 %) under optimal conditions were close to the predicted values, verifying the optimization process. Aeration (2.5 vvm for 4 h) increased viable cell counts and decreased glycerol production (a by-product), but not fermentation efficiency. An osmoprotectant (40  mM potassium chloride combined with 10 mM potassium hydroxide, KCl/KOH) at 30 °C had no positive effect on ethanol fermentation efficiency. However, at 25 °C, the osmoprotectant increased PE from 106 to 116 g/L and ethanol yield from 0.46 to 0.49 g/g. At 35–37 °C, it prolonged cell viability, increasing PE by 5–12 g/L and %SC by 3–8 % without affecting ethanol yield. However, at 39 °C, no positive impact occurred on ethanol fermentation efficiency. The findings from this study, particularly the optimized fermentation conditions and stress tolerance strategies, could guide the scale-up to an industrial level of bioethanol production from sweet sorghum stem juice or other feedstocks using VHG fermentation, contributing to the development of more efficient and sustainable biofuel production processes.